Experimental study of subcooled flow boiling heat transfer of water in a circular channel under one-side heating conditions. (April 2018) - Zhu, Ge; Bi, Qincheng; Yan, Jianguo; Lv, Haicai
Highlights: An electrically heated method was used to simulate one-side heating conditions. The effects of the parameters on the heat transfer coefficients have been discussed in detail. A serious of correlations of subcooled flow boiling were assessed with the experimental results. A modified correlation was proposed to predict the heat transfer coefficients under one-side heating conditions. Abstract: Heat transfer experiments on subcooled water flow boiling were carried out in a vertical upward circular channel, which was set off-center in a rectangular nickel block. Particular attention was paid to the heat transfer of water under high and heat fluxes and high mass fluxes under one-side heating conditions, with respect to the heat removal technologies for the divertor in the International Thermonuclear Experimental Reactor (ITER). The test section was electrically heated by a large AC power supply with an effective heated length of 360 mm. The test parameters covered pressures of 3–5 MPa, mass fluxes of 3000–8000 kg·m −2 ·s −1, inlet bulk temperatures of 40–220 °C, and equivalent heat fluxes up to 8 MW·m −2 . The effects of the parameters on the heat transfer coefficients have been discussed in detail, from single-phase forced convention to fully developed nucleate boiling. A series of heat transfer correlations were evaluated using the experimental data, and most of the correlations did not adequately fit the experimental results. A modified Liu-Winterton correlation and modified Jens-Lottes correlation were used to predict the heat transfer coefficients in the partially boiling region and fully developed boiling region, respectively. The average errors (AEs) of the two correlations were −0.28% and 0.6%, and the root mean square errors (RMSEs) of them were 7.93% and 2.89%.